OP131 Cost-Effectiveness Of Dexamethasone And Adalimumab For Uveitis. (12th January 2018) - Squires, Hazel; Poku, Edith; Cooper, Katy; Stevens, John; Hamilton, Jean; Wong, Ruth; Bermejo, Inigo
Abstract : INTRODUCTION: Uveitis is inflammation inside the eye whose underlying cause may be infectious or non-infectious. The objective of our study was to assess the cost-effectiveness of the dexamethasone implant and adalimumab compared with current practice (immunosuppressants and systemic corticosteroids) in patients with non-infectious intermediate, posterior or pan-uveitis. METHODS: A Markov model was built to estimate costs and benefits of the interventions. Systematic reviews were performed to identify the relevant evidence. Quality of life data collected in three key randomized-controlled trials (1-3) was used to estimate the interventions effectiveness compared with the trials comparator arms, which consisted of placebo plus limited current practice (LCP). An indirect treatment comparison between adalimumab and dexamethasone was considered inappropriate due to lack of necessary evidence. For adalimumab, patients with active and inactive uveitis were considered separately. Due to the short duration of the trials, the rate of blindness, an important complication of uveitis, was highly uncertain. Substantial exploratory analyses were therefore undertaken. The analysis was performed from the perspective of the National Health Service (NHS) and Personal Social Services (PSS). Costs were calculated based on standard United Kingdom sources. RESULTS: The estimated incremental cost-effectiveness (ICER) of dexamethasone compared with LCP was GBP19, 509 per quality-adjusted life year (QALY) gained. The estimated ICER of adalimumab compared with LCP was GBP94, 523 and GBP317, 547 per QALY in patients with active and inactive uveitis respectively. The factors with the largest impact upon the ICERs were the rate of blindness and the proportion of cases of blindness avoided by interventions. CONCLUSIONS: Dexamethasone and adalimumab resulted in health gains, but at significant extra costs, especially adalimumab which is unlikely to be considered a cost-effective use of NHS resources. The results of the analysis are highly uncertain due to the limited availability of evidence on: the comparative effectiveness of dexamethasone, adalimumab and current practice; the effectiveness of treatments in avoiding blindness; and, the effectiveness of interventions in different subgroups.